Impact of the McDonald Criteria 2017 on Early Diagnosis of Relapsing-Remitting Multiple Sclerosis - Schwenkenbecher, Philipp; Wurster, Ulrich; Konen, Franz Felix; Gingele, Stefan; Sühs, Kurt-Wolfram; Wattjes, Mike P.; Stangel, Martin; Skripuletz, Thomas (Frontiers in Neurology, 2019)
Multiple sclerosis is a chronic immune mediated demyelinating disease leading to neurological disabilities unless diagnosed and treated early. Guidelines on MS diagnosis and monitoring experienced comprehensive changes over the last decades. The first McDonald criteria published in 2001 emphasized the importance of MR imaging but also recognized the role of cerebrospinal fluid diagnostics. The demonstration of an intrathecal immunoglobulin G synthesis is a well-established additional component and has a long tradition in the diagnosis of relapsing-remitting multiple sclerosis. However, the role of cerebrospinal fluid for diagnostic purposes was rather diminished in each revision of the McDonald criteria. In the latest revision of the McDonald criteria of 2017, the detection of an intrathecal immunoglobulin G synthesis as oligoclonal bands experienced a revival. Patients with the first clinical event suggesting multiple sclerosis who fulfill the criteria for dissemination in space can be diagnosed with relapsing-remitting multiple sclerosis when oligoclonal bands in cerebrospinal fluid are detected. The aim of this review article is to evaluate the role of oligoclonal bands in the application of McDonald criteria of 2017 regarding the facilitation of an accurate diagnosis.